Effects of zinc oxide nanoparticles transformation in sulfur-containing water on its toxicity to microalgae: Physicochemical analysis, photosynthetic efficiency and potential mechanisms. (1st September 2022) - Zhang, Hong; Miao, Chunguang; Huo, Zhipeng; Luo, Tianzhi
Highlights: ZnO NPs transformed in sulfur-containing water were investigated. Sulfidation drastically changed the toxicity of ZnO NPs to Chlorella sorokiniana . Zinc ions and neoformations play a major role in toxicity in different stages. Transformed products have profound effects on algal photosynthesis by shading. Abstract: The environmental transformation of nanomaterials will have a significant impact on their ecotoxicity. Sulfidation process is one of the most important transformation processes in the aquatic environment. Although the sulfidation of ZnO nanoparticles (ZnO NPs) has been previously reported, the transformation characteristics and the relationship between the transformation process and toxicity mechanism to aquatic organisms, especially microalgae, require further study. Therefore, we systematically investigated the transformation properties of ZnO NPs in sulfur-containing water and its impact on the toxicity to microalgae. The results showed that the transformation products of ZnO NPs mainly contained ZnS nanoparticles, and their contents increased with the increase of sulfur-zinc molar ratio in the aqueous solution. After the first week of treatment, the sulfidized ZnO NPs showed less toxicity to microalgae than the pristine ZnO NPs, and interestingly, they exhibited higher toxicity over time. The zinc ions and transformation products played a major role in different treatment periods, resulting in different toxicity. The results of photosynthetic pigments, photosynthetic efficiency, and the relative electron transport rates indicated that the sulfidation process of ZnO NPs had a remarkable influence on algal photosynthesis. These newly acquired results will help us explore the transformation characteristics of ZnO NPs and reasonably assess their potential risks in the aquatic environment. Graphical abstract: Image, graphical abstract